Different mercury bioaccumulation kinetics by two macrobenthic species: The bivalve Scrobicularia plana and the polychaete Hediste diversicolor - Cardoso, P. G. (2009)
Mercury is a global priority pollutant and given its huge relevance in terms of environmental damage and a threat to human health, it is important to study the bioaccumulation processes at the level of macrobenthic organisms and evaluate possible consequences for the trophic chain. In this work we evaluate the mercury accumulation rates of two distinct and economically important macrobenthic species, the polychaete Hediste diversicolor and the bivalve Scrobicularia plana, through a mesocosms laboratory experiment. The present experiment demonstrated different bioaccumulation kinetics for each species: while S. plana has a rapid accumulation after 48 h of exposure to contaminated sediments and then reaches a steady state, H. diversicolor has a linear mercury accumulation throughout the experiment time (31 days). The different patterns observed can be related to different feeding strategies and assimilation efficiencies. In addition, we can conclude that independently of the mercury concentration in the sediments, the two studied species in both contaminated sediments reached the same percentage (25%) of mercury accumulated at the end of the experiment when compared to the maximum concentrations recorded in the field. This experiment highlights that the mercury bioaccumulation rate by these two economically and ecologically important macrobenthic species is a reasonably rapid process which can promote serious consequences for the higher trophic levels, constituting a severe risk to the natural environment and ultimately to human health.